Indian economy under reforms as assessment of economic and social impact - Nagesh Kumar (Ed); Research and Information System for the Non-Alignmend and Other Developing Countries (New Delhi Bookwell, 2000)
The adoption of economic reforms by India in 1991 has attracted worldwide attention. The development community is curious if reforms will help the country in expediting her development process. While there is a consensus on the need for reforms, there hav
Keywords: Economics-India; Economic development; Economic policy